Correction: Ab initio calculation of energy levels of trivalent lanthanide ions - Freidzon, Alexandra Ya; Kurbatov, Ilia A; Vovna, Vitaliy I (Physical chemistry chemical physics : PCCP, 2018)
Correction for 'Ab initio calculation of energy levels of trivalent lanthanide ions' by Alexandra Ya. Freidzon et al., Phys. Chem. Chem. Phys., 2018, 20, 14564-14577.Correction for 'Ab initio calculation of energy levels of trivalent lanthanide ions' by Alexandra Ya. Freidzon et al., Phys. Chem. Chem. Phys., 2018, 20, 14564-14577.